Upholding the Right of Political Participation in Civil Society: an Overview of the Application of International Law and Standards - Qurrota A'yun; Syariful Alam (Yuridika, 2026)
Discrimination against civil society rights is still prevalent almost all over the world, including the right to participate in politics. A discussion on its enforcement is needed, reviewed based on the application of existing international laws and standards. The expected benefit of making this paper is to stabilize and provide efforts against the challenges of enforcing the right of political participation by civil society subjects through international standards. The method used to analyze the writing is a literature review of journals, books and reliable sources. The purpose of this paper is to reduce the discrimination related to political activities or the processes of certain groups by dissecting the factors of discrimination regarding the political participation of civil society and clarifying the challenges or evaluations present for international organizations, who have an important role in the enforcement of rights, especially universal human rights. This paper indicates that every society has the same right to participate in politics, so there should be no difference in treatment for certain groups of people. It also explains that there are still many violations of rights and discrimination in the political sphere.